ANALISIS PERENCANAAN PEMBANGUNAN EKONOMI KABUPATEN KUTAI KARTANEGARA - nur, ferdian (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This study aims to identify potential and competitive sectors, shifts in economicstructure and economic development planning strategies in Kutai KartanegaraRegency. The data used in this study are Gross Regional Domestic Product (GDP)at Constant Prices in 2010 for East Kalimantan Province in 2010-2020 and datafor Gross Regional Domestic Product (GDP) at Constant Prices in 2010 in KutaiKartanegara Regency in 2010-2020. The analytical model used is KlassenTypology Analysis, Shift Share Analysis and SWOT Analysis. The results of this study are that between 2010-2020 of the 17 sectors of Kutai KartanegaraRegency, only the mining and quarrying sector is included in the depressed anduncompetitive sector. In the period 2010-2020 there has been a shift in theregional economic structure where the sectoral contribution to the shift in totalgrowth in GDP for the primary sector is 15.31 percent, the secondary sector is42.77 percent and the tertiary is 41.91 percent. The economic developmentplanning strategy that needs to be taken is the development of regional economiccenters based on the renewable sector and competitive superior commodities, thedevelopment of a digital and creative economic ecosystem in order to supportincreased production and added value as well as the competitiveness of leadingsectors, improving the quality of human and institutional resources communityeconomy, Development of integrated and equitable connectivity and infrastructuredevelopment, Increasing the competitiveness of regional investment as well asReformulation of investment design based on the downstream of natural resourcesand Strengthening integration between potential sectors and regions in the contextof increasing the strong local value chain.